2021
DOI: 10.3390/ijerph18137211
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Labor Using Tocolysis as a Possible Risk Factor for Postpartum Depression: A 14-Year Population-Based Study in Taiwan

Abstract: Postpartum depression (PPD) is associated with negative physical and mental health outcomes for the mother and infant. Women often experience elevated symptoms of PPD, and the incidence of PPD has increased in recent years. There were lack of studies to investigate the effects of medications during pregnancy. Herein, we focused on the most common obstetric medical therapies used in labor and determined whether the medical therapies cause mental stress in pregnant women. This 14-year retrospective population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…None of these agents was considered capable of inducing the occurrence of psychiatric symptoms. Liu et al [ 20 ] performed a 14-year retrospective study and found that ritodrine treatment for preterm labor was a significant risk factor for postpartum depression, especially in the form of an injection. This study lets us link the psychiatric symptoms of the patient in the present study with ritodrine.…”
Section: Discussionmentioning
confidence: 99%
“…None of these agents was considered capable of inducing the occurrence of psychiatric symptoms. Liu et al [ 20 ] performed a 14-year retrospective study and found that ritodrine treatment for preterm labor was a significant risk factor for postpartum depression, especially in the form of an injection. This study lets us link the psychiatric symptoms of the patient in the present study with ritodrine.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Global Health Observatory by the World Health Organization, complications of prematurity are a leading cause of death under 5 years of age, with 964,366 deaths in 2017 alone, accounting for 17.8% of the under-5-mortality globally [ 6 , 7 ]. Furthermore, preterm birth is a great burden to the healthcare system as well as a source of substantial financial and psychological hardship [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%